Kondycja psychiczna młodzieży akademickiej - polsko-turecka analiza porównawcza = Mental health of university students - a Polish-Turkish comparative analysis - Nowicka, Agnieszka; Skorobogata, Magdalena (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article presents the results of a Polish-Turkish comparative analysis of the mental health of university students in the context of contemporary social, political, and economic crises. The study was conducted among pedagogy students at the University of Wrocław and Hacettepe University in Ankara, using a diagnostic survey method and a questionnaire developed for this purpose.
Keywords: kondycja psychiczna; młodzież akademicka; badania porównawcze; Polska; Turcja; mental health; university students; comparative research; Poland; Turkey